PENGARUH MODEL LATIHAN METODE HALANGAN TERHADAP KETEPATAN POINTING HIGH LOB JARAK 7 METER PADA ATLET MAHASISWA JPOK FKIP UNIVERSITAS LAMBUNG MANGKURAT - Amirudin, Muhammad; Dirgantoro, Edwin Wahyu; Rakhman, Arie (Universitas Hamzanwadi, 2024)
The high lob throwing technique in the game of pétanque is b, which is a bosi throw with a parabolic height. For this pointing, you have to pay attention to several things. The Bosi comes out above 110 degrees, the Bosi falls near the boka 0.5 – 1 M. The aim of the research is to determine the level of accuracy of Pointing using the High Lob Technique in pétanque athletes of JPOK FKIP Lambung Mangkurat University students. Researchers use the Drill method in the form of training students when carrying out étanqu activities repeatedly. The sample population in this study was Petanque athletes, Physical Education Students at Lambung Mangkurat University who had taken part in PORPROV, totaling 8 people and who would be treated 14 times. From testing the data obtained which was carried out in the SPSS 23 application, we can display the results of testing the influence of the obstacle method on the high lob throwing technique. It can be seen from the results of the paired t test data that it was obtained (sig) of 0.000. This value is also smaller than the value of 0.05, which when practicing the Obstacle method can influence the accuracy of the throw in the high lob technique. Conclusions based on the results of data analysis in the form of using an obstacle method in the form of a 1.5 meter high water pipe have a significant and related influence on supporting the accuracy of high lob technique throws in pétanque games for JPOK FKIP Student athletes at Lambung Mangkurat University